The Use Of Pulse Field GelElectrophoresis For Megaplasmid Isolatioan Of Pseudomonas solanacearum - Siti Subandiyah; Triwibowo Yuwono; Wayan T. Artama (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1994)
-